1992
DOI: 10.1128/cmr.5.2.120
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal capillariasis

Abstract: Intestinal capillariasis caused by Capillaria philippinensis appeared first in the Philippines and subsequently in Thailand, Japan, Iran, Egypt, and Taiwan, but most infections occur in the Philippines and Thailand. As established experimentally, the life cycle involves freshwater fish as intermediate hosts and fish-eating birds as definitive hosts. Embryonated eggs from feces fed to fish hatch and grow as larvae in the fish intestines. Infective larvae fed to monkeys, Mongolian gerbils, and fish-eating birds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
75
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(78 citation statements)
references
References 14 publications
2
75
1
Order By: Relevance
“…Mebendazole, in a dose of 100 mg twice daily is an acceptable alternative, but needs to be given for 20 days, and relapses are more frequent with this drug [8].…”
Section: Capillariasismentioning
confidence: 99%
“…Mebendazole, in a dose of 100 mg twice daily is an acceptable alternative, but needs to be given for 20 days, and relapses are more frequent with this drug [8].…”
Section: Capillariasismentioning
confidence: 99%
“…The delay was over a year in our cases. It has been found that Capillaria species are closely related to Trichuris and Trichinella species [1] , and the eggs of Trichuris trichiura and C. philippinensis are similar in appearance, although they can be differentiated by experienced observers [17] . Some individuals could be infected with both parasites, which further confuse the picture.…”
Section: Discussionmentioning
confidence: 99%
“…Capillaria species parasitize many classes of vertebrates, although only 4 species described have been found in humans, namely Capillaria phillippinensis, Capillaria plica, Capillaria aerophila, and Capillaria hepatica [1] . C. philippinensis is a tiny nematode that was first described in the 1960 s as the causative agent of severe diarrheal syndromes in humans.…”
Section: Introductionmentioning
confidence: 99%
“…6). P. philippinensis is a rare cause of malabsorption that occurs as a consequence of eating raw or insufficiently cooked fish harboring the larvae [1,2]. As the eggs of P. philippinensis are excreted sporadically in feces, multiple stool samples may be required to establish the diagnosis [2].…”
mentioning
confidence: 99%
“…P. philippinensis is a rare cause of malabsorption that occurs as a consequence of eating raw or insufficiently cooked fish harboring the larvae [1,2]. As the eggs of P. philippinensis are excreted sporadically in feces, multiple stool samples may be required to establish the diagnosis [2]. In cases where stool samples fail to identify the parasite, enteroscopy and jejunal biopsy, as well as microscopic examination of the aspirated jejunal contents can help to establish the diagnosis [2].…”
mentioning
confidence: 99%